Recognition of Emotions for People with Autism: An Approach to Improve Skills. (15th January 2022) - Dantas, Adilmar Coelho; do Nascimento, Marcelo Zanchetta
Abstract : Autism spectrum disorder refers to a neurodevelopmental disorders characterized by repetitive behavior patterns, impaired social interaction, and impaired verbal and nonverbal communication. The ability to recognize mental states from facial expressions plays an important role in both social interaction and interpersonal communication. Thus, in recent years, several proposals have been presented, aiming to contribute to the improvement of emotional skills in order to improve social interaction. In this paper, a game is presented to support the development of emotional skills in people with autism spectrum disorder. The software used helps to develop the ability to recognize and express six basic emotions: joy, sadness, anger, disgust, surprise, and fear. Based on the theory of facial action coding systems and digital image processing techniques, it is possible to detect facial expressions and classify them into one of the six basic emotions. Experiments were performed using four public domain image databases (CK+, FER2013, RAF-DB, and MMI) and a group of children with autism spectrum disorder for evaluating the existing emotional skills. The results showed that the proposed software contributed to improvement of the skills of detection and recognition of the basic emotions in individuals with autism spectrum disorder.